TurkuNLP Entry for Interactive Bio-ID Assignment - Suwisa Kaewphan; Farrokh Mehryary; Kai Hakala; Tapio Salakoski; Filip Ginter (United States, 2025)
We participate in BioCreative VI: Interactive Bio-ID Assignment (Bio-ID) track by developing systems capable of named entity recognition and normalization of 6 entity types, namely Protein, Cell, Organism, Tissue, Molecule and Cellular. Our named entity recognition system is based on conditional random fields. For named entity normalization, we apply fuzzy matching and rule-based system to disambiguate and assign unique identifiers to the entities. The official evaluation shows that average F1-scores of all entity types for our recognition and normalization systems on strict span offsets are 0.720 and 0.668, respectively.
Proceedings of the BioCreative VI Workshop